The effect of foam rolling on recovery between two eight hundred metre runs - D`Amico, A.; Paolone, V. (Journal of Human Kinetics, 2017)
With the increased popularity of foam rolling as a means of recovery, it is important to establish the exact manner in which the practice is useful. The purpose of this study was to examine the impact of foam rolling on recovery between two 800 m runs. Sixteen trained males (mean ± sd; age, 20.5 ± .5 yr; average 800 m treadmill run time, 145.2 ± 1.8 s) participated in the study, using a randomized, crossover design. The subjects completed two 800 m runs on a treadmill, separated by a 30 min rest, during which time a foam rolling protocol or passive rest period was performed. The speed of each run was as fast as possible. Subjects had access to speed controls, but were blinded to the actual speed. Blood lactate concentration and V.CO2 were measured prior to and following each run. Stride length, 800 m run time, and hip extension were measured during each run. V.CO2, stride length, 800 m run time, and hip extension were not significantly different between conditions (p > .05). For blood lactate, no statistical interaction was found between condition and time (p > .05). Foam rolling between two 800 m runs separated by 30 min performed by trained male runners does not alter performance.